Diurnal Variations in the Aphelion Cloud Belt as Observed by the Emirates Exploration Imager (EXI). Issue 18 (26th September 2022) - Wolff, Michael J.; Fernando, Anton; Smith, Michael D.; Forget, François; Millour, Ehouarn; Atwood, Samuel A.; Jones, Andrew R.; Osterloo, Mikki M.; Shuping, Ralph; Al Shamsi, Mariam; Jeppesen, Christian; Fisher, Charles
Abstract: Observations by the Emirates eXploration Imager (EXI) on‐board the Emirates Mars Mission are used to characterize the diurnal, seasonal, and spatial behavior of aphelion cloud belt during Mars Year 36 L S  ∼ 30°–190°. Building from previous work with the Mars Color Imager (MARCI) onboard the Mars Reconnaissance Orbiter, we retrieve water ice extinction optical depth ( τ ice ) with an uncertainty ±0.0232 (excluding particle size effects). We connect EXI and MARCI using radiance and τ ice . Zonal and meridional diurnal trends are analyzed over 6–18 hr Local True Solar Time. The retrievals show large morning‐evening asymmetries about a minimum near 12 hr. The latitudinal distributions in early morning are extensive and particularly striking near mid‐summer. Comparisons to the Mars Planetary Climate Model show reasonable agreement with basic diurnal behavior, but noticeable departures include too much water ice in early morning, the general latitudinal extent, and behavior at smaller scales like the volcanoes and other topographically distinct features. Plain Language Summary: Water ice clouds have important roles in the Martian atmosphere because they can influence weather and act as probes of important weather and climate processes. Using the camera on‐board the Emirates Mars Mission, water ice clouds are studied for the first time throughout the Martian day and year at scales of 10–20 km around the planet. We study a key cloud structure called the aphelion cloud belt (ACB) that encircles the planet at low latitudes during the northern hemisphere spring and summer seasons. Using the camera images from this period, we examine how the ACB structure changes from morning through evening and throughout these two seasons. We developed a computer program that converts the brightness of a pixel into a measure of the cloud thickness. We find that the ACB clouds are much thicker and wide‐spread in the early morning compared to other times of day; and are much more extant across the planet in the morning, particularly in mid‐summer. We also compare to weather prediction programs and find important differences that will help scientists improve Mars weather forecasts for future research and missions. Key Points: The Emirates eXploration Imager is used to retrieve ice extinction optical depth in Mars Year 36 during solar longitudes 30–190° Diurnal trends of the aphelion cloud belt are examined between 6 and 18 hr using both zonal and meridional maps, revealing new behavior Comparisons to the Mars Planetary Climate Model show reasonable agreement with broad structure, but important differences are noted